The contribution of Buddhist Monks to the creation of Palm Leaf Manuscripts - Nishanthi, M; Chandani, J.G.; Konpola, K.W.A.M.; Kumara, H.U.C.S. (Department of Pali and Buddhist Studies, University of Sri Jayewardenepura, 2025)
In the past, writing on palm leaf manuscripts has been a rich and enduring tradition in Sri Lanka, and palm leaf manuscripts are one of Sri Lanka's foremost historical sources. However, natural palm leaves are not suitable for scribing on palm leaf manuscripts and it is a very difficult task to make it suitable for writing. Several steps must be taken to create a palm leaf manuscript from marking the palm tree for palm leaves to writing on palm leaf using a steel point and blackened. The contribution of Buddhist monks in this respect has been very high since ancient times. However, a review of investigations, research articles, and surveys on the subject showed that there was no discussion of Buddhist monks' potential contributions to many aspects of the process of creating palm leaf manuscripts. Therefore, the objective of the study was to investigate in more detail what contribution the Buddhist monks’ creations to palm leaf manuscripts. Sources such as books, journal articles, conference papers, websites and case studies published on palm leaf manuscripts were used to conduct this literature review. All literature selected for research was analyzed based on the process of creating palm leaf manuscripts. After the Tripitaka was written completely in the text on the palm leaves in the first century BC at Aluvihara (also known as Alokavihara in Pali), many palm leaf manuscripts were prepared and spread throughout the island. In Sri Lanka, a lot of Tipitaka manuscripts are written in Pali Language using Sinhalese characters. It is evident from the analytical literature that both lay and priests worked based on the temple to create the palm leaf manuscripts. However, the study revealed that Buddhist monks have contributed a lot to the writing of palm leaf manuscripts in Sri Lanka and that the process of creation is a Buddhist religious activity. Large scale religious writing first appeared in the country when Ven. Buddhaghosa Composed the Aṭṭhakathā (commentaries) in the fifth century AD. The Buddhist manuscripts such as Chullavaggaya and Visuddhimaggaṭīkā, Mahāsatipaṭṭhāna-suttha, Abhidhammapiṭaka, Dhammapada atthakatha, Dhammapada, Dighanikaya, Theragāthā and Vimānavatthu show that the Buddhist monks have contributed to the creation of Buddhist manuscripts by widely using palm leaves.
a literature review
Keywords: Palm-lea, Manuscripts, Steel point, Blackened, Tipitaka